ANALYSIS OF THE PERFORMANCE OF FARMERS MEMBERS OF THE COMBINED FARMER GROUPS IN THE APPLICATION OF THE INTERNAL CONTROL SYSTEM (ICS) IN PADDY ORGANIC CULTIVATION IN TASIKMALAYA REGENCY - Achmad Tjachja Nugraha; Ujang Maman; Hanifa Hanifa (Syarif Hidayatullah State Islamic University Jakarta, 2021)
This research is backgrounded by the need for environmentally friendly agricultural management, namely by implementing organic agriculture. The International Federation of Organic Agriculture Movements (IFOAM) has developed a way of group certification through the implementation of the Internal Control System (ICS) to address the issue of the cost of farmer group-scale certification. The Simpatico Gapoktan located in Thetically Regency is a Gapoktan that has implemented ICS since 2008. However, behind the success of the certification, some farmer groups did not pass the certification, so the number of members decreased from year to year. The unsuccessfulness of farmer groups in certification needs to be analyzed, one of which is by analyzing the performance of farmers in the application of ICS. This study aims to analyze the expectations and performance of Simpatik Gapoktan members in the application of ICS to organic rice cultivation systems and risk control management, as well as the application of organic internal standards, ICS documentation, and training. The results of this study showed that the level of suitability in the application of the organic rice cultivation system obtained an overall average statement of 87.41%. This is not appropriate because the performance achievements of farmers have not met expectations. The level of conformity between the expectations and performance of farmers members of the Simpatik Gapoktan in the implementation of risk control management with a total conformity level VI value of 84.58% is considered to have not met the expectations of farmers. The level of conformity between farmers' expectations and performance in the implementation of organic internal standards with a conformity level of 74.24% has not met farmers' expectations. For ICS documentation, the total conformity level value of 73.6% has not met the expectations of farmers, and training with a conformity level value of 84.25% has also not met the expectations of farmers.